Study abroad pathways: Supply chain dynamics in sending students from Punjab to Canada - Kaur, Tanveen; Mehra, Anjali (Journal of International Students, 2025)
In recent years, the growing demand for international education, coupled with economic challenges in Punjab, has driven a significant increase in students seeking higher education in Canada. This paper examines the roles of two critical stakeholders in this process: the Canadian government and overseas education agents. Canada’s policies on work permits and pathways to permanent residency make it a highly attractive destination, while education agents in Punjab play a pivotal role in facilitating student migration through financial incentives and targeted marketing strategies. Structured in two sections, this study explores Canadian policy impacts and the strategies employed by education agents to channel students abroad. Findings underscore the importance of these interconnected dynamics in shaping Canada as a premier destination for Punjabi students.